IMF Staff papers : Volume 36 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1989)
The determinants of current account imbalances under floating exchange rates are analyzed. The analysis provides a framework within which the sources of. and the remedies for, the current account imbalances between the United States, Japan, and the Federal Republic of Germany can be discussed. The effects of various government policies are emphasized, in particular the differences between expenditure-changing and expenditure-switching policies. Short-run and long-run considerations are investigated, as well as the role played by expectations and price-level dynamics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet